Intermediate-term outcomes of the Aurolab aqueous drainage implant in neovascular glaucoma. Issue 3 (29th September 2021) - Gnanavelu, Subathra; Puthuran, George Varghese; Chiranjeevi, Kousalya Pavani; Wijesinghe, Hiruni Kaushalya; Reddy, Vishnuvardhan; Mani, Iswarya; Krishnadas, Subbaiah Ramasamy; Gedde, Steven Jon
Abstract : Purpose: To assess the outcomes of the non-valved Aurolab aqueous drainage implant (AADI) in neovascular glaucoma (NVG). Methods: Data of consecutive patients with NVG who underwent AADI and had a minimum follow-up of 2 years were included. The primary outcome measure was the cumulative rate of surgical failure defined as intraocular pressure (IOP) >21 mm Hg or reduced <20% below baseline, IOP ≤5 mm Hg, reoperation for glaucoma or a complication, or loss of light perception vision. Results: We included 85 eyes of 85 patients with NVG, with a mean age of 61.2±9.3 years. The most common aetiologies were proliferative diabetic retinopathy (n=43) and central retinal vein occlusion (n=24). The mean IOP decreased from 36.8±12.5 mm Hg at baseline to 15.8±7.5 mm Hg at 2-year follow-up (p<0.001) and the number of IOP-lowering medications reduced from 3.4±0.8 to 1.5±1.1 (p<0.001). The cumulative rate of failure increased from 3.1% (95% CI 1.1% to 11.8%) at 1 year to 33.8% (95% CI 20.4% to 52.5%) at 2 years. Multivariable analysis showed that eyes with open angles had a lower risk of failure (HR 0.17, 95% CI 0.10 to 1.03, p=0.09). The logarithm of minimum angle of resolution visual acuity declined from 0.98±0.7 to 1.8±1.0 at 2 years (p<0.001). Conclusion: Approximately one-third of NVG eyes that received the AADI failed after 2 years of follow-up similar to other series. Early AADI implantation at the open angle stage of NVG may yield better results.